Shape Dependent Therapeutic Potential of Nanoparticulate System: Advance Approach for Drug Delivery - Verma, Shristy; Malviya, Rishabha; Srivastava, Saurabh; Ahmad, Irfan; Singh, Bhupinder; Almontasheri, Rasha; Uniyal, Prerna (Current Pharmaceutical Design, 2024)
Drug delivery systems rely heavily on nanoparticles because they provide a targeted and monitored release of pharmaceuticals that maximize therapeutic efficacy and minimize side effects. To maximize drug internalization, this review focuses on comprehending the interactions between biological systems and nanoparticles. The way that nanoparticles behave during cellular uptake, distribution, and retention in the body is determined by their shape. Different forms, such as mesoporous silica nanoparticles, micelles, and nanorods, each have special properties that influence how well drugs are delivered to cells and internalized. To achieve the desired particle morphology, shape-controlled nanoparticle synthesis strategies take into account variables like pH, temperatures, and reaction time. Top-down techniques entail dissolving bulk materials to produce nanoparticles, whereas bottom-up techniques enable nanostructures to self-assemble. Comprehending the interactions at the bio-nano interface is essential to surmounting biological barriers and enhancing the therapeutic efficacy of nanotechnology in drug delivery systems. In general, drug internalization and distribution are greatly influenced by the shape of nanoparticles, which presents an opportunity for tailored and efficient treatment plans in a range of medical applications.
Keywords: bottom-up approach